Фольклор, література, політика: хорватсько-українські аналогії - Пащенко, Є. (Народна творчість та етнологія, 2011)
Starting out from comparison with Krleža’s observations on Croatian political folklore from World War I, the paper points to the large fund of Ukrainian oral creativity expressing a critical stance towards the political events in Ukraine from 1918 onwards. Polazeći od usporedbi z Krležinim opažanjima o hrvatskom političkom folkloru iz Prvoga svjetskog rata, rad upućuje na veliki fond ukrajinskog usmenog stvaralaštva u kojem se izražava kritičan stav prema političkim događajima u Ukrajini od 1918.